Primary Tubercular Parotitis - Dubey, Tulika; Tulachan, Bishwo; Borgohain, BN; Rai, Sabina (Journal of Universal College of Medical Sciences, 2015)
This is a case report of a 50 years old female who was diagnosed as primary tubercular parotitis. The clinical presentation was similar to that of a parotid neoplasm. She was treated with anti tubercular therapy.Tubercular parotitis is a very rare entity even in the countries where tuberculosis is highly prevelant. The presentation being similar to a neoplasm may bring about diagnostic dilemma and the patient may have to undergo unnecessary surgery. So in cases where we encounter a chronic parotid swelling, we have to be highly suspicious in diagnosing and a thorough workup in the line of tuberculosis has to be done even in the absence of clinically evident foci of tuberculosis elsewhere. Ultrasonography (USG) and Fine Needle Aspiration Cytology (FNAC) prove to be very useful in diagnosing such cases and these cases are better treated medically. Journal of Universal College of Medical Sciences Vol. 3, No. 1, 2015: 48-50